2018
DOI: 10.1242/dev.157222
|View full text |Cite|
|
Sign up to set email alerts
|

Amniotic ectoderm expansion occurs via distinct modes and requires SMAD5-mediated signalling

Abstract: Upon gastrulation, the mammalian conceptus transforms rapidly from a simple bilayer into a multilayered embryo enveloped by its extra-embryonic membranes. Impaired development of the amnion, the innermost membrane, causes major malformations. To clarify the origin of the mouse amnion, we used single-cell labelling and clonal analysis. We identified four clone types with distinct clonal growth patterns in amniotic ectoderm. Two main types have progenitors in extreme proximal-anterior epiblast. Early descendants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 61 publications
1
32
0
Order By: Relevance
“…Moreover, even though the mouse does not develop an amniotic sac structure at all and begins amnion formation after gastrulation begins, BMP signaling is critical for amniogenesis in that model as well. In mice, BMP ligands are expressed at the embryonic/extraembryonic border of the cup-shaped cylinder, and Smad5 mutants show defects in that border, as well as aberrant amnion and chorion development (Pereira et al, 2011; Dobreva et al, 2018). A recent detailed clonal analysis of amniotic ectoderm progenitors in the mouse shows that these cells arise from the epiblast cells at this border and expand both anteriorly and posteriorly (Dobreva et al, 2018).…”
Section: Amniogenesis and Amniotic Sac Formation: Establishment Of Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, even though the mouse does not develop an amniotic sac structure at all and begins amnion formation after gastrulation begins, BMP signaling is critical for amniogenesis in that model as well. In mice, BMP ligands are expressed at the embryonic/extraembryonic border of the cup-shaped cylinder, and Smad5 mutants show defects in that border, as well as aberrant amnion and chorion development (Pereira et al, 2011; Dobreva et al, 2018). A recent detailed clonal analysis of amniotic ectoderm progenitors in the mouse shows that these cells arise from the epiblast cells at this border and expand both anteriorly and posteriorly (Dobreva et al, 2018).…”
Section: Amniogenesis and Amniotic Sac Formation: Establishment Of Thmentioning
confidence: 99%
“…In mice, BMP ligands are expressed at the embryonic/extraembryonic border of the cup-shaped cylinder, and Smad5 mutants show defects in that border, as well as aberrant amnion and chorion development (Pereira et al, 2011; Dobreva et al, 2018). A recent detailed clonal analysis of amniotic ectoderm progenitors in the mouse shows that these cells arise from the epiblast cells at this border and expand both anteriorly and posteriorly (Dobreva et al, 2018). Loss of Smad5 compromises both clonal expansion of these progenitors and squamous morphogenesis of their progeny.…”
Section: Amniogenesis and Amniotic Sac Formation: Establishment Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…While important insights have been obtained by extracting and manipulating embryos ex vivo, key contributions might come from the very mechanical and geometrical constraints imposed by the uterus itself (Hiramatsu et al, 2013;Matsuo and Hiramatsu, 2017). Indeed, it has been found that the mechanics (i.e., the mechanical properties, forces, and strains) of the extraembryonic environment or of the embryo proper directly underpin key developmental events such as AP (Hiramatsu et al, 2013) or LR axis establishment (Chien et al, 2018), notochord emergence (Imuta et al, 2014), or amnion development (Dobreva et al, 2018;Shao et al, 2017) in multiple embryonic systems. Moreover, direct links between mechanics and developmental events have been drawn and shown to be evolutionarily conserved (Brunet et al, 2013;Pukhlyakova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Deflation experiments by Imuta et al (2014) have shown for example that the anisotropic forces exerted on the EPI by the expansion of the amniotic cavity drives the convergent-extension of cells during notochord morphogenesis ( Figure 1C). Additionally, mechanotransducing pathways have been posited to feed into the oscillatory networks driving somitogenesis (Hubaud et al, 2017) and mechanical cues may even guide the development of the amnion, in mouse as in human (Dobreva et al, 2018;Shao et al, 2017;Taniguchi et al, 2018). Even more interestingly, mechanosensitive gene expression has been documented in various developmental models (Brunet et al, 2013) as well as in sea anemones where prolonged embryo compression licenses ectopic expression of the gastrulation marker T/Brachyury (T/Bra) (Pukhlyakova et al, 2018).…”
Section: Introductionmentioning
confidence: 99%